(untitled) (Journal of Pharmaceutical Negative Results, 2023)
There is only one planet, and it only has a certain number of resources. These resources are being used up much faster than they can be replenished, though. Clean land, fossil fuels, and the numerous plant and animal species that go extinct every year are examples of resources that cannot be reproduced. This study's goal is to review the literature on innovative marketing approaches and sustainable development, with a particular emphasis on how these approaches relate to the global environmental problems we are currently experiencing. In order to examine information, this conceptual work mostly leverages secondary data sources. According to the review, environmentally responsible marketing techniques can help firms and individuals while also encouraging sustainable growth. In addition, the weaknesses of the field, its future outlook, and potential research areas are examined. According to the study's findings, marketing, like other functional components of a company, contributes to the environmental problems the globe is currently facing. The developed economies have already caused damage, which now needs to be rectified. However, there is still time to prevent more environmental devastation, which offers a chance for the economies of emerging countries.